A business process model for blockchain-based South African real estate transactions - Tilbury, Jack Laurie (Rhodes University, Faculty of Commerce, Department of Information Systems, 2020)
The real estate transaction process has been described as inefficient and technologically outdated due to numerous stakeholders and predominantly paper-based operations. Despite the apparent bottlenecks in the current process, the implementation of new technology into the real estate sector has lagged. Several attempts have been made to modernise and digitise the business process but committed integration of assisting technology has lacked attention. This study examined the applicability and potential integration of blockchain technology into the business process of South African real estate transactions. Blockchain's novelty means that research in this space, especially within South Africa, is limited. Of the research that has been conducted, no models of the business processes for South African or blockchain-based real estate transactions have been constructed. This study provides two business process models, illustrating the two different processes. The main contribution of this paper was an integrated business process model, illustrating how the various processes and stakeholder interactions for South African blockchain-based real estate transactions are conducted on one transaction platform, common to all participating stakeholders. This platform was named the South African Blockchain Land Exchange System (SABLES), which manages and facilitates these transactions in their entirety from start to finish. This model depicts an enhanced business process that provides increased security, transparency, and speed. These benefits will be realised by those who register, adopt, and transact on the platform. Through in-depth interviews, the integrated business process model was assessed. The findings produced a final and combined thematic map, representing the main themes of the analysed interview data, namely blockchain implementation strategies, business process applicability, information technology assimilation, current transaction context, and PropTech 3.0 success factors. The discussion revealed that the current transaction process lacks technological innovation, which increases pressure on the conveyancing role. It was also revealed that there is not only a need within the industry, but a desire, for newer technologies to assist the transaction process. In order to streamline and improve efficiency, business processes should leverage digital records and data, and strive for a solution beyond digitisation, achieving digitalisation. Digitalisation recognises digital documents as official and legal documents as opposed to simply being digital back-ups. This, coupled with the business process models, represent theoretical contributions.
Keywords: Blockchains (Databases); Conveyancing -- Technological innovations; Real estate business -- Data processing; Real estate business -- South Africa -- Technological innovations